Naravovarstveno vrednotenje Radenskega polja pri Grosupljem na podlagi inventarizacije favne dnevnih metuljev (Lepidoptera: Rhopalocera) - Rebeušek, Franc (Natura Sloveniae, 2001)
Radensko polje is one of the largest areas of extensively used wet meadows in central Slovenia. In 2000, we surveyed the nature conservation value of this area based on distribution of the butterfly fauna. The presence of strong populations of Maculinea ažcon, Euphydryas aurinia and Pyrgus armoricanus pointed out a very high conservation value of the surveyed area. Equally important is the presence of locally distributed and highly threatened Carcharodus flocciferus in the northern part of the polje. In view of the evaluation of the endangered species distribution and the number of species recorded at the sites we propose two districts to be given the status of nature reserves, while the entire Radensko polje should be protected as a landscape park.
Keywords: environmental protection; metulji; ogroženost; Radensko polje; varstvo narave; zoogeografija